Correction: Brandão et al. Genotoxicity and Gene Expression in the Rat Lung Tissue following Instillation and Inhalation of Different Variants of Amorphous Silica Nanomaterials (aSiO2 NM). Nanomaterials 2021, 11, 1502 - Fátima Brandão; Carla Costa; Maria João Bessa; Elise Dumortier; Florence Debacq-Chainiaux; Roland Hubaux; Michel Salmon; Julie Laloy; Miruna S. Stan; Anca Hermenean; Sami Gharbia; Anca Dinischiotu; et al. (Nanomaterials)
In the original publication [...]